Principal Leadership Based on Justice and Tolerance Ethics in Vocational High Schools - Amiruddin Siahaan; Rizki Akmalia; Budi Suhartono; Rini Dewi Andriani; Mulkan Hasibuan (AL-ISHLAH: Jurnal Pendidikan, 2021)
This study aimed to determine the pattern of principals' leadership in implementing fair and tolerant leadership towards teachers and students who have different ethnicities, races, and religions. This study uses qualitative research methods, with the type of descriptive research. The subjects of this study were 6 teachers and 4 Vocational High School students. This study uses primary data and secondary data as data sources. At the same time, the data collection tools are through interviews, observation, and documentation. Data analysis techniques used are data reduction, data presentation, and concluding. The test of data validity is done by extending the period of observation, triangulation, and careful observation, and conducting member and checks so that the information obtained can be used in research in accordance with what was meant by the informant. Based on the findings, it is obtained that the principal's ethics of justice can be seen through the implementation of policies in his daily life, such as determining rewards and punishments based on fairness and tolerance regardless of race, ethnicity, and religion.